EVALUATION OF NON-STRUCTURAL INSTITUTION ESTABLISHMENT POLICY IN INDONESIA: CASES ON NATIONAL POLICE COMMISSION AND PROSECUTOR’S COMMISSION - Halilul Khairi (Sosiohumaniora, 2022)
The study examines non-structural government institutions/state auxiliary institutions in Indonesia, with a focus on the National Police Commission and the Prosecutor’s Commission. The data gathering method is qualitative through documentation and focuses group discussion (FGD). The purposes of this research are to examine the characteristics and performance measurements of the Police Commission and the Prosecutor’s Commission in achieving their objectives and to examine the policy performance evaluation of non-structural government institutions. Furthermore, the purpose of this research is to uncover critical characteristics that influence the performance of the Police Commission and the Prosecutor’s Commission in attaining their respective goals. The aim of the two commissions’ formation, as well as the independence of their institutions, are some of the measures used to evaluate their performance. According to the findings of this study, the Police Commission and the Prosecutor’s Commission are not yet entirely autonomous in carrying out their responsibilities as independent organizations. Furthermore, the National Police Commission’s and Prosecutor’s Commission’s objectives have not been met following the policy objectives that led to their foundation. The content of the policies created by the government, as well as the policy environment as an external feature, are essential aspects that impact the success of the Police Commission and the Prosecutor’s Commission in achieving their aims.